Perkembangan aplikasi teori pelanggaran harapan dalam berbagai konteks komunikasi: tinjauan pustaka sistematis - Firdha Yuni Gustia; Irwansyah Irwansyah (Jurnal Komunikasi Profesional, 2022)
Departing from interpersonal relationships that focus on nonverbal communication, it is interesting to see the use of expectancy violation theory (EVT) to analyze the wider context of communication in today's conditions, especially with the presence of new media and sophisticated technology. This study uses a systematic literature review method to explain the development of expectancy violation theory usage in the communication context over the last five years. After screening the articles, there were 31 articles using expectancy violation theory as one of the main theories. Based on the analysis of journal articles, most of the expectancy violation theory research was conducted in 2018 in the United States and discusses the concept of expectancy violation in general. In its development, until now, EVT is still relevant for various contexts, although the results are diverse because there are studies that reject the assumption of EVT. However, on the other hand, there is still a lot of research in EVT whose conceptual results vary but still support the theory.